2022
DOI: 10.1002/anie.202207230
|View full text |Cite
|
Sign up to set email alerts
|

Inside Cover: Dynamic Covalent Self‐Assembly of Chloride‐ and Ion‐Pair‐Templated Cryptates (Angew. Chem. Int. Ed. 28/2022)

Abstract: Angewandte ww ww ww ww ww ww www w w w. w. w. w an an a a a ge ge ge ge ge ge ge

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In 2023, von Delius et al reported the synthesis of trialkoxysilane cryptate-Na + complexes 39 and 40, utilizing the dynamic covalent reactivity of the SiÀ O bond (Scheme 13). [45] The reaction of trialkoxysilanes 41 and 42 with diethylene glycol 43 in the presence of a sodium cation under acidic conditions yielded the trialkoxysilane cryptate-Na + complexes 39 and 40, respectively. The molecular structures of these complexes were analyzed by X-ray crystallography.…”
Section: B) Bicycloalkanes With Silicon Bridgeheadsmentioning
confidence: 99%
“…In 2023, von Delius et al reported the synthesis of trialkoxysilane cryptate-Na + complexes 39 and 40, utilizing the dynamic covalent reactivity of the SiÀ O bond (Scheme 13). [45] The reaction of trialkoxysilanes 41 and 42 with diethylene glycol 43 in the presence of a sodium cation under acidic conditions yielded the trialkoxysilane cryptate-Na + complexes 39 and 40, respectively. The molecular structures of these complexes were analyzed by X-ray crystallography.…”
Section: B) Bicycloalkanes With Silicon Bridgeheadsmentioning
confidence: 99%
“…In recent years, several other dynamic covalent bond formations like siloxane exchange, and diketoenamines, have been applied in the design of vitrimer materials. [152][153][154][155][156] Figure 8. Vitrimers with a dynamic covalent cross-linking.…”
Section: Processable Thermosets (Covalent Adaptable Network Cans)mentioning
confidence: 99%
“…It is important to note the absence of protons in the exchange, which thus substantially differs from Si-OR/HO-R′ exchange under protic conditions. 38 We also added the first spectroscopic evidence for the spontaneous occurrence of a direct Si-O -bond metathesis, thus shedding light on the dynamic constitutional nature of the most common chemical bond in the Earth's crust. These insights have implications for catalysis and for environmental and materials science.…”
Section: Account Synlettmentioning
confidence: 99%